Analysis of the Grass and Legume cover, in and around Jalalgarh Farm of the Araria Plains in the Kosi Area - Chatterjee, B N; Dayal, B (Journal of Soil and Water Conservation, 2022)
The Ataria plains of the Purnea district in Bihar extend over an area of about 25,000 acres lying at about 250 511 N and 260 21’ N at 870 33’ E. The Jalalgarh farm, of about IOS.6 acres, is situated at an altitude of 144 ft above sea level in this plain. The soil is predominantly sandy and its depth varies from about 6" to 18M and below this layer there is continuous coarse sand only. About 150-200 years ago the Kosi river, which is also referred to as the ’river of sorrow of Bihar’ due to its frequent changes of its courses, used to flow in this area and now it in Saharsa has shifted towards the west, district.